Draft Genome Sequence of Altererythrobacter marensis DSM 21428(T), Isolated from Seawater - Cheng, Hong (Genome Announc, 2016)
Altererythrobacter marensis DSM 21428(T) was isolated from seawater collected around Mara Island, South Korea. The genomic characteristics of this strain support its potential for alkane-related compound degradation. A. marensis DSM 21428(T) has potential applications in bioremediation projects concerning offshore petroleum spill prevention and response.